Islam, Globalization, and Poverty Alleviation - Sulastyawati, Dwi (Al-Iqtishad: Journal of Islamic Economics, 2013)
Globalization is globab as well condition and situation, neither economically, politically, and socially. All countries that embrace open economic system have participated in the system of globalization. Today the world is under the influence of super power world. For instance, using dollar as the official currency for international transactions, so that dollar dominates in international transactions. As a result, the value of the debt of developing countries has increased due to the rising price of dollar. The increment of the debt value in developing countries led the government reduces subsidies for the community. Thus economic hardship perceived more and more for poor people. This resulted that poverty is hard to be alleviated. This article analyzes the various Islamic perspective and thoughts on the impact of globalization on poverty alleviation.DOI: 10.15408/aiq.v5i2.2123